Environmental Education and the challenges presented by the contemporary discourses about nature (Educação e Pesquisa, 2010)
The notion of nature has played an important role in philosophy and also in Environmental Education. Contemporary philosophers such as Gianni Vattimo and Newton Aquiles von Zuben declare that the notion of a single nature has contributed to the growth of a dogmatic metaphysics that has crystallized political and religious totalitarianisms. Environmental Education in Latin America has constituted a theoretical field and a privileged public space for the diffusion of non-dogmatic, non-totalitarian, notions of nature in close relationship to cultural and social diversity. At a first moment of Environmental Education the notion of nature was linked to natural resources. However, after specific themes related to the contemporary discourses about nature, such as transgenetics and biodiversity, have gained the public sphere we argue that Environmental Education has been facing new theoretical, political, ecological, social, cultural and pedagogical challenges. In the present article we try to identify and analyze some of these challenges, having as our theoretical foundation the ideas of Italian thinker Gianni Vattimo, and of Brazilian philosopher Newton Aquiles von Zuben, on the aspects related to bioethics and to the political role of education in the formation of citizens. We conclude that the approach to nature present in contemporary discourses helps to open out the dialogue between Environmental Education and bioethics, and to materialize it in daily social and pedagogical practices, thus representing a concrete alternative to allow citizens to face up to the challenges brought about by biodiversity and the transgenics with scientific, ethical and political arguments.